ACCELERATION OF DIGITAL-BASED PUBLIC SERVICES CASE STUDY AT THE INVESTMENT AND ONE-STOP INTEGRATED SERVICE OFFICE IN BELU DISTRICT - Joseph Franky Leto Bere (Suluh Adiluhung Publisher (SAPub), 2024)
The objective of this study was to analyze and describe the acceleration of public services at the Investment and One-Stop Integrated Service Office, analyze supporting and inhibiting factors, and formulate a digital-based public service model. The collection techniques were used to obtain accurate, actual and comprehensive data in accordance with the problems and focus of the study, such as interview, observation, and documentation. The results of the study showed a consistent tendency (trend) in public services in improving the performance of public service delivery in Belu District.